Diatom Species Richness in Algal Flora of Pamir, Tajikistan - Niyatbekov, Toirbek; Barinova, Sophia (European Scientific Journal, ESJ, 2018)
The main objective of this study was to quantify the diatom floral richness and analyze the diversity structure in Pamir aquatic habitats. We revealed 455 species (552 with infraspecific taxa) of diatom algae compiled from reference studies in 1930-1983 that was done for the first time, and our data after many floristic surveys conducted in the field during 2000-2015. Floristic analysis of the total species richness revealed 65 rare and 22 species new for Pamir algal flora, and has allowed us to identify prevailed Classes, Orders, and Families in the diatoms. Only four genera are prevailing and contain about 30% of total richness. The Pinnularia species from them are representing extremely large numbers (39). They prefer fresh, clear, circumneutral-water habitats in natural aquatic objects with developed phytoperiphytonic communities, included many rare species and can be peculiarities of the Pamir diatom flora.